The Eight Ujarait (Rocks) Model: Supporting Inuit Adolescent Mental Health With an Intervention Model Based on Inuit Ways of Knowing - Healey, Gwen Katheryn; Noah, Jennifer; Mearns, Ceporah (NEIHR National Coordinating Centre, 2016)
Objective: This study responded to a community-identified need to form an evidence base for interventions to promote mental health and wellness among youth in Nunavut. Methods: A literature review was conducted using the terms adolescence and Inuit and intervention or program or camp or land-based. PubMed and Google Scholar databases were used to find peer-reviewed and grey literature on community-based youth programs. The literature review was presented to parents, elders, and youth for discussion over several months in 2009-2010. Results: Key themes included: self-esteem, physical activity, stress and coping, positive peer relationships, Inuit identity, mental health and well-being, and the effects of intergenerational trauma on youth in Nunavut. Themes were incorporated into a model for youth mental health interventions based on Inuit terminology, philosophy, and societal values—the Eight Ujarait/Rocks Model. The model was implemented as a camp program in 6 pilots in 5 communities from 2011 to 2013. Data were collected before and after the camp. Results indicated that the program fostered physical, mental, emotional, and spiritual wellness among youth. Parent observations of participants included an improvement in behaviour and attitude, strong cultural pride, greater confidence in identity, and improved family and community relationships. Conclusion: Evidence-based, community-driven models for youth mental health interventions in the North hold promise. The application of one such model through a camp program had a lasting impact on the individuals involved, beyond their immediate participation. Long-term monitoring of the participants, and ongoing evaluations of camps as they continue to unfold across Nunavut, are needed to contribute to the robust evidence base for this program over time.